The relationship between skin function, barrier properties, and body‐dependent factors. Issue 2 (23rd October 2017) - Dąbrowska, A.K.; Spano, F.; Derler, S.; Adlhart, C.; Spencer, N.D.; Rossi, R.M.
Abstract: Background: Skin is a multilayer interface between the body and the environment, responsible for many important functions, such as temperature regulation, water transport, sensation, and protection from external triggers. Objectives: This paper provides an overview of principal factors that influence human skin and describes the diversity of skin characteristics, its causes and possible consequences. It also discusses limitations in the barrier function of the skin, describing mechanisms of absorption. Methods: There are a number of in vivo investigations focusing on the diversity of human skin characteristics with reference to barrier properties and body‐dependent factors. Results: Skin properties vary among individuals of different age, gender, ethnicity, and skin types. In addition, skin characteristics differ depending on the body site and can be influenced by the body‐mass index and lifestyle. Although one of the main functions of the skin is to act as a barrier, absorption of some substances remains possible. Conclusions: Various factors can alter human skin properties, which can be reflected in skin function and the quality of everyday life. Skin properties and function are strongly interlinked.